Preparation method of foamed nickel-based composite material for ozone photocatalytic treatment of oily sewage
By loading polydiphenyl terephthalene cyanoformate on the surface of the foam nickel matrix and inlaid with CdS/CdSm2S4 crystals, a large π-bonded conjugated polymer with superhydrophobic and supergasy-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-agrie-ag
Patent Information
- Application Number
- CN202411709294.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, when ozone treats oily sewage, ozone bubbles escape too quickly and stay time is too short, making it difficult to effectively oxidize and degrade oily sewage.
By loading polydiphenyl terephthalene cyanoformate on the surface of the foam nickel matrix and inlaid with CdS/CdSm2S4 crystals, a large π-bonded conjugated polymer with superhydrophobic and supergasy-agally compatible properties can be prepared, which can effectively adhere to ozone and extend its oxidative decomposition time with oil-containing wastewater.
The ozonation decomposition effect is significantly enhanced, and the performance of high-speed and high-efficiency photocatalytic oxidation synergistically degraded oil-containing wastewater is achieved.
Smart Images

Figure CN119524880A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of oily wastewater treatment, in particular to a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater. Background Art
[0002] Energy is an important factor in a country's economic and social development. A large amount of oily wastewater is generated during the process of oil extraction, processing and production. Oily wastewater not only pollutes water resources, but also poses a great threat to human health and the ecological environment.
[0003] Ozone has a high oxidation potential and strong oxidation characteristics. It has a strong ability to oxidize and degrade organic matter and can oxidize and decompose wastewater containing organic pollutants. However, in the process of ozone treatment of oily wastewater, ozone bubbles escape from the oily wastewater too quickly, the residence time is too short, and the interaction area with the organic oil in the oily wastewater is too small, making it difficult to effectively oxidize and degrade the oily wastewater.
[0004] Photocatalytic degradation of wastewater containing organic pollutants refers to the process in which photocatalytic materials absorb light energy under light conditions to produce active substances such as OH free radicals with high oxidizing ability, thereby oxidizing and degrading organic pollutants.
[0005] At present, the development of new materials that can effectively adhere to ozone and prolong its oxidative decomposition time with organic oil in oily wastewater, while increasing its action area, to enhance the ozonation decomposition effect, and have a photocatalytic oxidation synergistic effect, is a green and environmentally friendly technical approach to oily wastewater treatment. However, the oily wastewater treatment materials prepared by the existing technology have low degradation efficiency for organic oil and long treatment time, and cannot meet the requirements for rapid and efficient industrial degradation of oily wastewater. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater. The foamed nickel-based composite material prepared by the method has super-hydrophobic and super-aerophilic properties, can effectively adhere to ozone and prolong its oxidative decomposition time with organic oil in oily wastewater and increase its action area, can effectively enhance the ozonation decomposition effect, and has the performance of photocatalytic oxidation synergistically degrading oily wastewater at a high speed and high efficiency.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] The present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0009] Step [1]: Loading poly(diphenyl terephthalate) on the surface of the nickel foam substrate;
[0010] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate);
[0011] Step [3] embeds CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate.
[0012] Preferably, the step [1] specifically includes the following operations:
[0013] a1. Cumene hydroperoxide and cyclopentadiene are added to methanol and mixed to form an initiator solution; dimethyl terephthalate and 4-hydroxybenzoic acid phenyl ester are added to chloroform and mixed to form a base solution; the base solution and the initiator solution are mixed in a certain ratio to obtain a loading solution;
[0014] a2. The nickel foam sample is immersed in the loading liquid, heated in a water bath to 40-60°C, reacted for 10-12 hours, and dried at room temperature for 8 to 10 hours to obtain a nickel foam loaded with polyethylene terephthalate on the surface, recorded as intermediate A.
[0015] Preferably, in step a1, the amount of cumene hydroperoxide added to each liter of the initiator solution is 40-70 mL, and the amount of cyclopentadiene added is 10-20 mL; the amount of dimethyl terephthalate added to each liter of the base solution is 110-140 g, and the amount of 4-hydroxybenzoic acid phenyl ester added is 80-110 g; the volume ratio between the base solution and the initiator solution in the load solution is 5-7:2-3.
[0016] Preferably, in step a2, the weight of the nickel foam substrate immersed in each liter of the loading liquid is 180-220 g.
[0017] Preferably, the step [2] specifically includes the following operations:
[0018] b1. Add hydrogen cyanide, glycerol and hydroxylamine to deionized water and mix to form a synthetic liquid;
[0019] b2. The intermediate A is immersed in the synthetic solution, heated to 60-90°C, reacted for 6-10 hours, and dried at room temperature for 5 to 8 hours to obtain a nickel foam loaded with poly(diphenyl terephthalate) cyanoformate on the surface, which is recorded as intermediate B.
[0020] Preferably, the amount of hydroxylamine added to each liter of the synthetic liquid is 50-70 g, the concentration of hydrogen cyanide in the synthetic liquid is 120-150 mL / L, and the concentration of glycerol is 40-60 mL / L.
[0021] Preferably, the weight of the intermediate A immersed in each liter of the synthetic liquid is 50-80 g.
[0022] Preferably, the step [3] specifically includes the following operations:
[0023] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A; add ethyl mercaptan to ethanol and mix to form a composition liquid B; mix the composition liquid A and the composition liquid B in a certain proportion to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid, heat it in a water bath to 35-50°C, react for 4 to 6 hours, take out a sample, and record it as intermediate C;
[0024] c2. Add samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate to deionized water, mix to form a CdS / CdSm2S4 crystal mosaic forming solution, immerse the intermediate C in the CdS / CdSm2S4 crystal mosaic forming solution, heat in a water bath to 40-60°C, react for 3-5 hours, dry at room temperature for 4-8 hours, and finally obtain the foamed nickel-based composite material.
[0025] Preferably, in step c1, the concentration of cadmium nitrate in the composition liquid A is 50-70 g / L, and the concentration of sodium thiosulfate is 40-60 g / L; the concentration of ethyl mercaptan in the composition liquid B is 120-140 mL / L; the volume ratio between the composition liquid A and the composition liquid B in the CdS crystal reaction liquid is 3-5:1-2; and the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 220-260 g.
[0026] Preferably, in step c2, the amount of samarium trichloride added to each liter of the CdS / CdSm2S4 crystal mosaic forming liquid is 80-100 g, the amount of cadmium nitrate added is 40-60 g, the amount of sodium trifluoromethanesulfinate added is 15-30 g, the amount of dodecylbenzenesulfonic acid added is 30-50 mL, and the amount of ammonium thiosulfate added is 40-80 g; the weight of the intermediate C immersed in each liter of the CdS / CdSm2S4 crystal mosaic forming liquid is 140-190 g.
[0027] The positive effects of the present invention are as follows: the nickel foam-based composite material prepared according to the method of the present invention is prepared by synthesizing poly(diphenyl terephthalate) cyanoacrylate) organic matter on the surface of nickel foam and inlaying it to form CdS / CdSm2S4 crystals, wherein poly(diphenyl terephthalate) cyanoacrylate is synthesized by replacing hydroxyl and cyano groups of poly(diphenyl terephthalate) compounds, and poly(diphenyl terephthalate) is prepared by polymerizing dimethyl terephthalate monomers and 4-hydroxybenzoic acid phenyl ester monomers. Among them, the benzene ring of the main chain of poly(phenyl terephthalate) cyanoformate has a large π bond and conjugation effect, and has high stability; in addition, poly(phenyl terephthalate) cyanoformate has a low surface energy and has super hydrophobic and super aerophilic properties, which can effectively adhere to ozone and prolong its oxidative decomposition time with organic oil in oily wastewater and increase its action area, thereby enhancing the ozonation decomposition effect; CdS crystals are hexagonal phases with a space group of P63mc, CdSm2S4 crystals have a cubic crystal structure and belong to the space group Fd-3m, CdS / CdSm2S4 crystals have the characteristics of wide absorption spectra of visible light and ultraviolet light, CdS has the advantages of a narrow band gap, a suitable energy band position and a wide range of visible light absorption, CdSm2S4 crystals not only have the advantages of a wide ultraviolet absorption spectrum, but their electronic structure can also effectively inhibit the recombination of photogenerated electrons and holes in CdS, and have excellent photocatalytic activity.
[0028] In summary, the nickel-based foam composite material prepared according to the present invention has super-hydrophobic and super-aerophilic properties, can effectively adhere to ozone and prolong its oxidative decomposition time with organic oil in oily wastewater and increase its action area, can effectively enhance the ozonation decomposition effect, and has the performance of photocatalytic oxidation synergistically degrading oily wastewater at a high speed and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the preparation process of the foamed nickel-based composite material of the present invention;
[0030] Figure 2 is a schematic diagram of the structure of the intermediate A of the present invention;
[0031] Figure 3 is a schematic structural diagram of the foamed nickel-based composite material of the present invention;
[0032] Figure 4a , 4b 4c are comparison diagrams of surface wetting angles of Example 1, Comparative Example 1 and Comparative Example 2 in air at different ozone concentrations and different oily wastewaters;
[0033] Figure 5a , 5b 5a and 5b are the corresponding TOC removal rates when using Example 1, Comparative Example 1 and Comparative Example 2 to treat oily wastewater. DETAILED DESCRIPTION
[0034] Reference Figure 1 The present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0035] Step [1] loading polydiphenyl terephthalate on the surface of the nickel foam substrate specifically comprises the following operations:
[0036] a1. Add cumene hydroperoxide and cyclopentadiene to methanol and mix to form an initiator solution, wherein the amount of cumene hydroperoxide added to each liter of the initiator solution is 40 to 70 mL, and the amount of cyclopentadiene added is 10 to 20 mL; dimethyl terephthalate and phenyl 4-hydroxybenzoate are added to chloroform to form a base solution, wherein the amount of dimethyl terephthalate added to each liter of the base solution is 110 to 140 g, and the amount of phenyl 4-hydroxybenzoate added is 80 to 110 g; the base solution and the initiator solution are mixed in a volume ratio of 5 to 7:2 to 3 to obtain a loading solution;
[0037] a2. Immerse the nickel foam sample in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid is 180-220 g), heat it in a water bath to 40-60° C., react for 10-12 hours, and dry it at room temperature for 8 to 10 hours to obtain a nickel foam loaded with poly(diphenyl terephthalate) on the surface, which is denoted as intermediate A. The schematic diagram of its microstructure is shown in FIG. Figure 2 shown.
[0038] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0039] b1. Add hydrogen cyanide, glycerol and hydroxylamine to deionized water and mix to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 50 to 70 g, the concentration of hydrogen cyanide in the synthetic liquid is 120 to 150 mL / L, and the concentration of glycerol is 40 to 60 mL / L;
[0040] b2. Immerse the intermediate A in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 50-80 g), heat to 60-90°C, react for 6-10 hours, and dry at room temperature for 5 to 8 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoformate loaded on the surface, which is recorded as intermediate B.
[0041] Step [3] embedding CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate, specifically comprises the following operations:
[0042] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A having a cadmium nitrate concentration of 50 to 70 g / L and a sodium thiosulfate concentration of 40 to 60 g / L; add ethyl mercaptan to ethanol and mix to form a composition liquid B having an ethyl mercaptan concentration of 120 to 140 mL / L; mix the composition liquid A and the composition liquid B in a volume ratio of 3 to 5:1 to 2 to form a CdS crystal reaction solution; immerse the intermediate B in the CdS crystal reaction solution (the amount of the intermediate C immersed in each liter of the CdS crystal reaction solution is 220-260 g), heat in a water bath to 35-50 ° C, react for 4 to 6 hours, remove the sample, and record it as intermediate C;
[0043] c2. The samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate are added to deionized water and mixed to form a CdS / CdSm2S4 crystal mosaic forming solution, wherein the amount of samarium trichloride added per liter of the CdS / CdSm2S4 crystal mosaic forming solution is 80 to 100g, cadmium nitrate is added in an amount of 40 to 60g, sodium trifluoromethanesulfinate is added in an amount of 15 to 30g, dodecylbenzenesulfonic acid is added in an amount of 30 to 50mL, and ammonium thiosulfate is added in an amount of 40-80 g; immersing the intermediate C in the CdS / CdSm2S4 crystal mosaic forming solution (the weight of the intermediate C immersed in each liter of the CdS / CdSm2S4 crystal mosaic forming solution is 140-190 g), heating in a water bath to 40-60° C., reacting for 3-5 hours, and drying at room temperature for 4-8 hours to finally obtain the foamed nickel-based composite material (foamed nickel-based CdS / CdSm2S4 crystal @ poly(diphenyl terephthalate) cyanoformate), the microstructure schematic diagram of which is shown in FIG. Figure 3 shown.
[0044] The preferred embodiments of the present invention are described below by way of example.
[0045] Example 1
[0046] Preferred embodiment 1 of the present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0047] Step [1]: loading polydiphenyl terephthalate on the surface of the nickel foam substrate, specifically comprising the following operations:
[0048] a1. Cumene hydroperoxide and cyclopentadiene were added to methanol and mixed to form an initiator solution, wherein the amount of cumene hydroperoxide added per liter of the initiator solution was 65 mL and the amount of cyclopentadiene added was 14 mL; dimethyl terephthalate and phenyl 4-hydroxybenzoate were added to chloroform and mixed to form a base solution, wherein the amount of dimethyl terephthalate added per liter of the base solution was 130 g and the amount of phenyl 4-hydroxybenzoate added was 90 g; the base solution and the initiator solution were mixed in a volume ratio of 5:2 to obtain a loading solution;
[0049] a2. The nickel foam sample was immersed in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid was 190 g), heated to 55° C. in a water bath, reacted for 10 hours, and dried at room temperature for 9 hours to obtain a nickel foam with polyethylene terephthalate loaded on the surface, which was recorded as intermediate A.
[0050] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0051] b1. Adding hydrogen cyanide, glycerol and hydroxylamine to deionized water and mixing to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 60 g, the concentration of hydrogen cyanide in the synthetic liquid is 140 mL / L, and the concentration of glycerol is 50 mL / L;
[0052] b2. The intermediate A is immersed in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 70 g), heated to 80°C, reacted for 9 hours, and dried at room temperature for 7 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoformate loaded on the surface, which is recorded as intermediate B.
[0053] Step [3] embedding CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate, specifically comprises the following operations:
[0054] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A with a cadmium nitrate concentration of 65 g / L and a sodium thiosulfate concentration of 50 g / L; add ethyl mercaptan to ethanol and mix to form a composition liquid B with an ethyl mercaptan concentration of 130 mL / L; mix the composition liquid A and the composition liquid B in a volume ratio of 5:2 to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid (the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 255 g), heat in a water bath to 40°C, react for 5 hours, take out a sample, and record it as intermediate C;
[0055] c2. Add samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate to deionized water and mix to form a CdS / CdSm2S4 crystal mosaic forming solution, wherein the amount of samarium trichloride added per liter of the CdS / CdSm2S4 crystal mosaic forming solution is 90g, the amount of cadmium nitrate added is 50g, the amount of sodium trifluoromethanesulfinate added is 25g, the amount of dodecylbenzenesulfonic acid added is 40mL, and the amount of ammonium thiosulfate added is 70g; the intermediate C is immersed in the CdS / CdSm2S4 crystal mosaic forming solution (the weight of the intermediate C immersed in the CdS / CdSm2S4 crystal mosaic forming solution is 175g per liter), heated to 55°C in a water bath, reacted for 4 hours, and dried at room temperature for 6 hours to finally obtain the foamed nickel-based composite material, recorded as Example 1.
[0056] Comparative Example 1
[0057] This comparative example 1 provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0058] Step [1] loading polydiphenyl terephthalate on the surface of the nickel foam substrate specifically comprises the following operations:
[0059] a1. Add cumene hydroperoxide and cyclopentadiene to methanol and mix to form an initiator solution, wherein cumene hydroperoxide is added in an amount of 45 mL and cyclopentadiene is added in an amount of 15 mL per liter of the initiator solution; dimethyl terephthalate and phenyl 4-hydroxybenzoate are added to chloroform and mixed to form a base solution, wherein dimethyl terephthalate is added in an amount of 120 g and phenyl 4-hydroxybenzoate is added in an amount of 90 g per liter of the base solution; the base solution and the initiator solution are mixed in a volume ratio of 5:2 to obtain a loading solution;
[0060] a2. The nickel foam sample was immersed in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid was 200 g), heated to 45° C. in a water bath, reacted for 11 hours, and dried at room temperature for 9 hours to obtain a nickel foam with polyethylene terephthalate loaded on the surface, which was recorded as intermediate A.
[0061] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0062] b1. Adding hydrogen cyanide, glycerol and hydroxylamine to deionized water and mixing to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 60 g, the concentration of hydrogen cyanide in the synthetic liquid is 130 mL / L, and the concentration of glycerol is 50 mL / L;
[0063] b2. The intermediate A is immersed in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 70 g), heated to 70°C, reacted for 7 hours, and dried at room temperature for 6 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoformate loaded on the surface, which is recorded as intermediate B.
[0064] Step [3] embedding CdS crystals on the surface of the poly(diphenyl terephthalate)cyanoformate, specifically comprises the following operations:
[0065] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A with a cadmium nitrate concentration of 60 g / L and a sodium thiosulfate concentration of 50 g / L; add ethyl mercaptan to ethanol and mix to form a composition liquid B with an ethyl mercaptan concentration of 130 mL / L; mix the composition liquid A and the composition liquid B in a volume ratio of 5:2 to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid (the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 240 g), heat to 40°C in a water bath, react for 5 hours, take out the sample, and finally obtain a foamed nickel-based composite material (foamed nickel-based CdS crystal @ poly(diphenyl terephthalate)), which is recorded as Comparative Example 1.
[0066] Comparative Example 2
[0067] This comparative example 2 provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0068] Step [1] loading polydiphenyl terephthalate on the surface of the nickel foam substrate specifically comprises the following operations:
[0069] a1. Add cumene hydroperoxide and cyclopentadiene to methanol and mix to form an initiator solution, wherein cumene hydroperoxide is added in an amount of 60 mL and cyclopentadiene is added in an amount of 18 mL per liter of the initiator solution; dimethyl terephthalate and phenyl 4-hydroxybenzoate are added to chloroform and mixed to form a base solution, wherein dimethyl terephthalate is added in an amount of 130 g and phenyl 4-hydroxybenzoate is added in an amount of 100 g per liter of the base solution; the base solution and the initiator solution are mixed in a volume ratio of 7:3 to obtain a loading solution;
[0070] a2. The nickel foam sample was immersed in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid was 200 g), heated to 50° C. in a water bath, reacted for 10 hours, and dried at room temperature for 8 hours to obtain a nickel foam with polyethylene terephthalate loaded on the surface, which was recorded as intermediate A.
[0071] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0072] b1. Adding hydrogen cyanide, glycerol and hydroxylamine to deionized water and mixing to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 55 g, the concentration of hydrogen cyanide in the synthetic liquid is 130 mL / L, and the concentration of glycerol is 45 mL / L;
[0073] b2. The intermediate A is immersed in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 60 g), heated to 80°C, reacted for 7 hours, and dried at room temperature for 6 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoformate loaded on the surface, which is recorded as Comparative Example 2.
[0074] In order to analyze the performance of photocatalytic and ozone synergistic decomposition and oxidation of organic oil in oily wastewater in Example 1, Comparative Example 1 and Comparative Example 2, chloroform, n-heptane and vacuum pump oil were added to deionized water to form three kinds of simulated oily wastewater (the amount of chloroform or n-heptane or vacuum pump oil added in each liter of simulated oily wastewater was 200 mg). 10g of Example 1, Comparative Example 1 and Comparative Example 2 were added to 100ml of chloroform, n-heptane and vacuum pump oil simulated oily wastewater, and the ozone generated by the ozone generator was input into the above three simulated oily wastewaters, respectively, and the ozone input concentration was adjusted to 10mg / L, 20mg / L and 30mg / L respectively. Using a xenon lamp light source under the conditions of working current 20A and working voltage 20V, ultraviolet light (λ=350nm) and visible light (λ=530nm) were irradiated to Comparative Example 1, Comparative Example 2 and Example 1 for thirty minutes, and a dark control group without light was set at the same time.
[0075] The contact angle measuring instrument was used to measure the surface wetting angle of oily wastewater in the air in Comparative Example 1, Comparative Example 2 and Example 1, and the contact angle of ozone bubbles in each simulated oily wastewater on the surface of Comparative Example 1, Comparative Example 2 and Example 1 when the input concentration of ozone was 10 mg / L, 20 mg / L and 30 mg / L. The surface wetting angle test results are shown in FIG. Figure 4a -c, it can be seen from the figure that the surface wetting angles of Comparative Example 1, Comparative Example 2 and Example 1 are all greater than 150°, and Comparative Example 1, Comparative Example 2 and Example 1 all have super hydrophobic properties, and in the simulated oily wastewater with input ozone concentrations of 10 mg / L, 20 mg / L and 30 mg / L, the contact angles of ozone bubbles on the surfaces of Comparative Example 1, Comparative Example 2 and Example 1 are all about 0°, and Comparative Example 1, Comparative Example 2 and Example 1 all have super aerophilic properties.
[0076] The TOC removal rates of the simulated oily wastewater treated in Comparative Example 1, Comparative Example 2 and Example 1 under ultraviolet and visible light conditions are as follows: Figure 5a-c, as shown in the figure, the total organic carbon (TOC) removal rate of Example 1 under ultraviolet and visible light irradiation by photocatalysis and ozone synergistic decomposition of chloroform, n-heptane and vacuum pump oil simulated oily wastewater reached more than 90%, which is significantly higher than the TOC removal rate of Comparative Example 1 and Comparative Example 2 under the same conditions by photocatalysis and ozone synergistic decomposition of chloroform, n-heptane and vacuum pump oil simulated oily wastewater (respectively 72-85%, 34-44%). The total organic carbon (TOC) removal rates of Example 1, Comparative Example 1 and Comparative Example 2 for treating chloroform, n-heptane and vacuum pump oil simulated oily wastewater in the dark without light and only with ozone decomposition are all 32-49%.
[0077] In summary, the nickel-based foam composite material prepared according to the present invention has super-hydrophobic and super-aerophilic properties, can effectively adhere to ozone and prolong its oxidative decomposition time with organic oil in oily wastewater and increase its action area, can effectively enhance the ozonation decomposition effect, and has the performance of photocatalytic oxidation synergistically degrading oily wastewater at a high speed and high efficiency.
[0078] To illustrate in further detail, three additional examples are provided below.
[0079] Example 2
[0080] Preferred embodiment 2 of the present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0081] Step [1]: loading polydiphenyl terephthalate on the surface of the nickel foam substrate, specifically comprising the following operations:
[0082] a1. Cumene hydroperoxide and cyclopentadiene were added to methanol and mixed to form an initiator solution, wherein the amount of cumene hydroperoxide added per liter of the initiator solution was 40 mL and the amount of cyclopentadiene added was 20 mL; dimethyl terephthalate and 4-hydroxybenzoic acid phenyl ester were added to chloroform and mixed to form a base solution, wherein the amount of dimethyl terephthalate added per liter of the base solution was 110 g and the amount of 4-hydroxybenzoic acid phenyl ester added was 80 g; the base solution and the initiator solution were mixed in a volume ratio of 7:2 to obtain a loading solution;
[0083] a2. The nickel foam sample was immersed in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid was 180 g), heated to 60° C. in a water bath, reacted for 10 hours, and dried at room temperature for 10 hours to obtain a nickel foam with polyethylene terephthalate loaded on the surface, which was recorded as intermediate A.
[0084] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0085] b1. Adding hydrogen cyanide, glycerol and hydroxylamine to deionized water and mixing to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 50 g, the concentration of hydrogen cyanide in the synthetic liquid is 120 mL / L, and the concentration of glycerol is 60 mL / L;
[0086] b2. The intermediate A is immersed in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 50 g), heated to 90°C, reacted for 6 hours, and dried at room temperature for 5 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoacrylate loaded on the surface, which is recorded as intermediate B.
[0087] Step [3] embedding CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate, specifically comprises the following operations:
[0088] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A with a cadmium nitrate concentration of 70 g / L and a sodium thiosulfate concentration of 40 g / L; add ethyl mercaptan to ethanol and mix to form a composition liquid B with an ethyl mercaptan concentration of 140 mL / L; mix the composition liquid A and the composition liquid B in a volume ratio of 3:1 to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid (the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 220 g), heat in a water bath to 35°C, react for 6 hours, take out a sample, and record it as intermediate C;
[0089] c2. Add samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate to deionized water and mix to form a CdS / CdSm2S4 crystal mosaic forming solution, wherein the amount of samarium trichloride added per liter of the CdS / CdSm2S4 crystal mosaic forming solution is 100g, the amount of cadmium nitrate added is 40g, the amount of sodium trifluoromethanesulfinate added is 15g, the amount of dodecylbenzenesulfonic acid added is 30mL, and the amount of ammonium thiosulfate added is 40g; immerse the intermediate C in the CdS / CdSm2S4 crystal mosaic forming solution (the weight of the intermediate C immersed in the CdS / CdSm2S4 crystal mosaic forming solution is 140g per liter), heat to 40°C in a water bath, react for 5 hours, and dry at room temperature for 8 hours to finally obtain the foamed nickel-based composite material.
[0090] Example 3
[0091] Preferred embodiment 3 of the present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0092] Step [1]: loading polydiphenyl terephthalate on the surface of the nickel foam substrate, specifically comprising the following operations:
[0093] a1. Adding cumene hydroperoxide and cyclopentadiene to methanol, mixing to form an initiator solution, wherein the amount of cumene hydroperoxide added per liter of the initiator solution is 70 mL, and the amount of cyclopentadiene added is 10 mL; adding dimethyl terephthalate and 4-hydroxybenzoic acid phenyl ester to chloroform, mixing to form a base solution, wherein the amount of dimethyl terephthalate added per liter of the base solution is 140 g, and the amount of 4-hydroxybenzoic acid phenyl ester added is 110 g; the base solution and the initiator solution are mixed in a volume ratio of 5:3 to obtain a loading solution;
[0094] a2. The nickel foam sample was immersed in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid was 220 g), heated to 40° C. in a water bath, reacted for 12 hours, and dried at room temperature for 8 hours to obtain a nickel foam with polyethylene terephthalate loaded on the surface, which was recorded as intermediate A.
[0095] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0096] b1. Adding hydrogen cyanide, glycerol and hydroxylamine to deionized water and mixing to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 70 g, the concentration of hydrogen cyanide in the synthetic liquid is 150 mL / L, and the concentration of glycerol is 40 mL / L;
[0097] b2. The intermediate A is immersed in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 80 g), heated to 60°C, reacted for 10 hours, and dried at room temperature for 8 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoformate loaded on the surface, which is recorded as intermediate B.
[0098] Step [3] embedding CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate, specifically comprises the following operations:
[0099] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A with a cadmium nitrate concentration of 50 g / L and a sodium thiosulfate concentration of 60 g / L; add ethyl mercaptan to ethanol and mix to form a composition liquid B with an ethyl mercaptan concentration of 120 mL / L; mix the composition liquid A and the composition liquid B in a volume ratio of 5:2 to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid (the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 260 g), heat in a water bath to 50°C, react for 4 hours, take out the sample, and record it as intermediate C;
[0100] c2. Add samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate to deionized water and mix to form a CdS / CdSm2S4 crystal mosaic forming solution, wherein the amount of samarium trichloride added per liter of the CdS / CdSm2S4 crystal mosaic forming solution is 80g, the amount of cadmium nitrate added is 60g, the amount of sodium trifluoromethanesulfinate added is 30g, the amount of dodecylbenzenesulfonic acid added is 50mL, and the amount of ammonium thiosulfate added is 80g; immerse the intermediate C in the CdS / CdSm2S4 crystal mosaic forming solution (the weight of the intermediate C immersed in the CdS / CdSm2S4 crystal mosaic forming solution is 190g per liter), heat to 60°C in a water bath, react for 3 hours, and dry at room temperature for 4 hours to finally obtain the foamed nickel-based composite material.
[0101] Example 4
[0102] Preferred embodiment 4 of the present invention provides a method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, comprising the following steps:
[0103] Step [1] loading polydiphenyl terephthalate on the surface of the nickel foam substrate specifically comprises the following operations:
[0104] a1. Add cumene hydroperoxide and cyclopentadiene to methanol and mix to form an initiator solution, wherein the amount of cumene hydroperoxide added per liter of the initiator solution is 55 mL and the amount of cyclopentadiene added is 15 mL; dimethyl terephthalate and phenyl 4-hydroxybenzoate are added to chloroform and mixed to form a base solution, wherein the amount of dimethyl terephthalate added per liter of the base solution is 125 g and the amount of phenyl 4-hydroxybenzoate added is 95 g; the base solution and the initiator solution are mixed in a volume ratio of 5:2 to obtain a loading solution;
[0105] a2. The nickel foam sample was immersed in the loading liquid (the weight of the nickel foam substrate immersed in each liter of the loading liquid was 200 g), heated to 50° C. in a water bath, reacted for 11 hours, and dried at room temperature for 9 hours to obtain a nickel foam with polyethylene terephthalate loaded on the surface, which was recorded as intermediate A.
[0106] Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate) comprises the following steps:
[0107] b1. Add hydrogen cyanide, glycerol and hydroxylamine to deionized water and mix to form a synthetic liquid; wherein the amount of hydroxylamine added per liter of the synthetic liquid is 60 g, the concentration of hydrogen cyanide in the synthetic liquid is 135 mL / L, and the concentration of glycerol is 50 mL / L;
[0108] b2. The intermediate A is immersed in the synthetic liquid (the weight of the intermediate A immersed in each liter of the synthetic liquid is 65 g), heated to 75°C, reacted for 9 hours, and dried at room temperature for 6 hours to obtain a nickel foam with poly(diphenyl terephthalate) cyanoacrylate loaded on the surface, which is recorded as intermediate B.
[0109] Step [3] embedding CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate, specifically comprises the following operations:
[0110] c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A with a cadmium nitrate concentration of 60 g / L and a sodium thiosulfate concentration of 50 g / L; add ethyl mercaptan to ethanol and mix to form a composition liquid B with an ethyl mercaptan concentration of 130 mL / L; mix the composition liquid A and the composition liquid B in a volume ratio of 3:2 to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid (the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 240 g), heat in a water bath to 45°C, react for 5 hours, take out the sample, and record it as intermediate C;
[0111] c2. Add samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate to deionized water and mix to form a CdS / CdSm2S4 crystal mosaic forming solution, wherein the amount of samarium trichloride added per liter of the CdS / CdSm2S4 crystal mosaic forming solution is 90g, the amount of cadmium nitrate added is 50g, the amount of sodium trifluoromethanesulfinate added is 25g, the amount of dodecylbenzenesulfonic acid added is 40mL, and the amount of ammonium thiosulfate added is 60g; immerse the intermediate C in the CdS / CdSm2S4 crystal mosaic forming solution (the weight of the intermediate C immersed in the CdS / CdSm2S4 crystal mosaic forming solution is 165g per liter), heat to 50°C in a water bath, react for 4 hours, and dry at room temperature for 6 hours to finally obtain the foamed nickel-based composite material.
[0112] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater, characterized in that: The following steps are included: Step [1]: Loading poly(diphenyl terephthalate) on the surface of the nickel foam substrate; Step [2] converting the poly (diphenyl terephthalate) into poly (diphenyl terephthalate hydroxycyanoacrylate); Step [3] embeds CdS / CdSm2S4 crystals on the surface of the poly(diphenyl terephthalate)cyanoformate.
2. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Cumene hydroperoxide and cyclopentadiene are added to methanol and mixed to form an initiator solution; dimethyl terephthalate and 4-hydroxybenzoic acid phenyl ester are added to chloroform and mixed to form a base solution; the base solution and the initiator solution are mixed in a certain ratio to obtain a loading solution; a2. The nickel foam sample is immersed in the loading liquid, heated in a water bath to 40-60°C, reacted for 10-12 hours, and dried at room temperature for 8 to 10 hours to obtain a nickel foam loaded with polyethylene terephthalate on the surface, recorded as intermediate A.
3. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 2, characterized in that: In step a1, the amount of cumene hydroperoxide added to each liter of the initiating solution is 40-70 mL, and the amount of cyclopentadiene added is 10-20 mL; the amount of dimethyl terephthalate added to each liter of the base solution is 110-140 g, and the amount of 4-hydroxybenzoic acid phenyl ester added is 80-110 g; the volume ratio between the base solution and the initiating solution in the loading solution is 5-7:2-3.
4. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 2, characterized in that: In step a2, the weight of the nickel foam substrate immersed in each liter of the loading liquid is 180-220 g.
5. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Add hydrogen cyanide, glycerol and hydroxylamine to deionized water and mix to form a synthetic liquid; b2. The intermediate A is immersed in the synthetic solution, heated to 60-90°C, reacted for 6-10 hours, and dried at room temperature for 5 to 8 hours to obtain a nickel foam loaded with poly(diphenyl terephthalate) cyanoformate on the surface, which is recorded as intermediate B.
6. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 5, characterized in that: The amount of hydroxylamine added to each liter of the synthetic liquid is 50-70 g, the concentration of hydrogen cyanide in the synthetic liquid is 120-150 mL / L, and the concentration of glycerol is 40-60 mL / L.
7. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 5, characterized in that: The weight of the intermediate A immersed in each liter of the synthetic liquid is 50-80 g.
8. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add cadmium nitrate and sodium thiosulfate to deionized water and mix to form a composition liquid A; add ethyl mercaptan to ethanol and mix to form a composition liquid B; mix the composition liquid A and the composition liquid B in a certain proportion to form a CdS crystal reaction liquid; immerse the intermediate B in the CdS crystal reaction liquid, heat it in a water bath to 35-50°C, react for 4 to 6 hours, take out a sample, and record it as intermediate C; c2. Add samarium trichloride, cadmium nitrate, sodium trifluoromethanesulfinate, dodecylbenzenesulfonic acid and ammonium thiosulfate to deionized water, mix to form a CdS / CdSm2S4 crystal mosaic forming solution, immerse the intermediate C in the CdS / CdSm2S4 crystal mosaic forming solution, heat in a water bath to 40-60°C, react for 3-5 hours, dry at room temperature for 4-8 hours, and finally obtain the foamed nickel-based composite material.
9. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 8, characterized in that: In step c1, the concentration of cadmium nitrate in the composition liquid A is 50-70 g / L, and the concentration of sodium thiosulfate is 40-60 g / L; the concentration of ethyl mercaptan in the composition liquid B is 120-140 mL / L; the volume ratio between the composition liquid A and the composition liquid B in the CdS crystal reaction liquid is 3-5:1-2; and the amount of the intermediate C immersed in each liter of the CdS crystal reaction liquid is 220-260 g.
10. The method for preparing a foamed nickel-based composite material for ozone photocatalytic treatment of oily wastewater according to claim 8, characterized in that: In step c2, the amount of samarium trichloride added to each liter of the CdS / CdSm2S4 crystal mosaic forming liquid is 80-100 g, the amount of cadmium nitrate added is 40-60 g, the amount of sodium trifluoromethanesulfinate added is 15-30 g, the amount of dodecylbenzenesulfonic acid added is 30-50 mL, and the amount of ammonium thiosulfate added is 40-80 g; the weight of the intermediate C immersed in each liter of the CdS / CdSm2S4 crystal mosaic forming liquid is 140-190 g.